Arctic journey:design experiments in the north - Miettinen, Satu; Jylkäs, Titta; Jeminen, Jaana; Tikkanen, Heikki; Vuorikari, Tytti Marianne (University of the Arctic, 2016)
168 UArctic Congress 2016, 12 - 16 S eptember, St. Petersburg, Russia Arctic journey – design experiments in the north Miettinen, Satu University of Lapland, Finland satu.miettinen@ulapland.fi Jylkäs, Titta, Jeminen, Jaana; Tikkanen , Heikki; Vuorikari , Tytti, University of Lapland, Finland This research paper is focusing on describing research outcomes of an Arctic Journey, a moving exhibition about personal human exp eriences. The exhibition experiments different forms of concretizing invisible elements and pursues to create a tangible experience of our Arctic lives. The exhibition aims to evoke thoughts about how each of us experiences and copes with our living condit ions and qualities, and how we relate to others in this sense. The exhibition is a platform for creating the arctic experience. The works of the exhibition are a collection from HumanSee - project team in University of Lapland and from the participatory wor kshops organized as a part on HumanSee - project. The project is focusing on service design research around the human experience. Exhibitions study alternative and unconventional forms for exhibitions and co - design processes that they enable. This research paper asks what is the role of co - design process when constructing the Arctic Journey? Further it asks how the use of multi - sensory production can enhance the represent ation of the arctic experience? The works incorporate both new and more traditional medi a in digital and printed form as well as with paper and textile. The exhibitions aims to gather information from the visitors on how the medias could be used as service design probes or other participatory means to improve businesses’ knowledge about their customers. The use of different media and service channels enable us to study the online and person to person interaction as well as audio part of the user experience. Exhibition has toured some of the main art and design universities Parsons the New Scho ol for Design, New York, Finlandia University, Hancock, MI, Emily Carr ...